The Development of Learning Activities According to the STEM Education to Promote Systems Thinking Skills of Students in Early Childhood Education - Onpuy, Wichayaporn (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2019)
This research aimed to1) design instructional model by using STEM Education, 2) compare students’ system thinking skill before and after attending activities, 3) develop students’ skill about activity design and integrated innovation activity by using STEM Education and 4) evaluate students’ satisfaction to ward satten ding activities. The samples applying cluster random sampling (using classroom as a sampling unit) consisted of 23 persons who are the third-year undergraduate students, majoring in Early Childhood at the Faculty of Education, Phetchabun Rajabhat University, in academic year 2018, second semester. The mean, standard deviation, and t–test dependent samples were applied to analyze the data. The finding of this research revealed as follows: 1) design and evaluate the instructional model by using STEM Education has 9 steps and this model was in the high level (=4.16), 2)the participants’ system thinking skill posttest was higher than pre test at the .05 level of statistical significance, 3) the participants were able to design activity and integrated innovation activity by using STEM Education as well and 4) the participants’ satisfaction toward attending activities was at the high level (=4.24).